Indo-West Pacific species of Trachinotus with spots on their sides as adults, with description of a new species endemic to the Marquesas Islands (Teleostei: Carangidae) - Smith-Vaniz, William F.; Walsh, Stephen J. (Zootaxa, 2019)
Diagnoses, comparisons, photographs and distribution maps are given for three previously described Indo-West Pacific species of Trachinotus that develop spots on their sides as adults. A new species, Trachinotus macrospilus, is described from the Marquesas Islands where it is endemic and the only species of the genus present. It differs from the other spotted Indo-West Pacific species most noticeably in having adults with only one or two large spots on each side, the largest spot larger than the iris diameter, and in having no large spot positioned above the pectoral fin. An identification key is given for all Indo-West Pacific species of Trachinotus and a molecular phylogeny, including 16 of the 20 valid species of Trachinotus is presented. A neotype is designated for Scomber botla Shaw, 1803.